DETERMINANTS AND CONSTRAINTS OF FARM RECORD-KEEPING PRACTICE AMONG SMALL-SCALE MILLET FARMERS IN BAUCHI STATE, NIGERIA - Musa, Abdul-Wahab Ahmad; Ado, Garba; Ahungwa, Gabriel Ternenge (FUDMA Journal of Sciences, 2026)
This study examined the determinants and constraints of farm record-keeping among small-scale millet farmers in Bauchi State, where millet production remains vital to rural livelihoods, but is characterized by low productivity and weak farm management practices. A multi-stage sampling technique was used to select 318 respondents from a population of 1,542 registered farmers, out of which 307 valid responses were analyzed. Data were analyzed using binary logistic regression and the Problem Confrontation Index (PCI). The results revealed that demographic factors such as age, education, farm size, and farming experience did not significantly influence record-keeping practices. In contrast, institutional and financial factors played a decisive role. Specifically, cooperative membership and access to credit significantly increased the likelihood of farmers keeping records, highlighting the importance of organized support systems and financial accountability in promoting better farm management. Regarding constraints, the study found that inaccessibility of digital tools and lacks of knowledge/skills were the most severe barriers to effective record-keeping. Other factors such as illiteracy, cost of materials, time constraints, and lack of interest were perceived as less severe. Overall, constraints were moderate, suggesting that farmers are not opposed to record-keeping but are limited by inadequate capacity and access to necessary tools. The study concludes that improving farm record-keeping requires strengthening institutional support through cooperatives, enhancing access to credit, and providing targeted training and digital tools. Such interventions are essential for improving farm management, increasing productivity, and enhancing the livelihoods of small-scale millet farmers.